KAJIAN LITERATUR: POTENSI EKSTRAK TERONG UNGU (SOLANUM MELONGENA L.) SEBAGAI AGEN ANTIOKSIDAN TERHADAP STRES OKSIDATIF HEPAR PADA MENOPAUSE - Ayu Made Ratna Dewi, Ida; Sugiritama, I Wayan; Made Linawati, Ni (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
Menopause is a physiological phase characterized by declining estrogen levels, contributing to increased oxidative stress resulting from an imbalance between the production of reactive oxygen species (ROS) and endogenous antioxidant defense systems. This condition can trigger cellular damage in various organs, including the liver, evidenced by elevated lipid peroxidation biomarkers—such as malondialdehyde (MDA)—and reduced activity of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Consequently, the use of natural antioxidants represents a potential approach to mitigating the impact of oxidative stress during menopause. Purple eggplant (*Solanum melongena* L.) is known to contain various bioactive compounds—notably anthocyanins (nasunin), flavonoids, and phenolic acids like chlorogenic acid—that exhibit antioxidant and hepatoprotective activities. This literature review aims to evaluate the bioactive potential of purple eggplant extract as a candidate for natural intervention against hepatic oxidative stress in menopausal conditions. The study involved a review of relevant scientific literature concerning menopause, hepatic oxidative stress, natural antioxidants, and the phytochemical composition of *Solanum melongena*. The findings indicate that bioactive compounds in purple eggplant extract have the potential to reduce oxidative stress through mechanisms such as free radical scavenging, inhibition of lipid peroxidation, and enhancement of endogenous antioxidant system activity. These effects are characterized by decreased MDA levels and increased activities of SOD, CAT, and GPx. Beyond direct antioxidant activity, the phytochemicals in purple eggplant may also modulate molecular pathways involved in cellular defense against oxidative stress. Thus, purple eggplant extract holds promise as a natural, phytochemical-based intervention to help prevent hepatic oxidative stress during menopause. However, further research—particularly human clinical trials—is required to confirm its efficacy and safety.